(RETRACTION ) Sunda Wiwitan Baduy: Agama Penjaga Alam Lindung di Desa Kenekes Banten - Masykur Wahid (Hikmah: Journal of Islamic Studies, 2011)
RETRACTION TO: WAHID, Masykur. Sunda Wiwitan Baduy: Agama Penjaga Alam Lindung di Desa Kenekes Banten. Hikmah: Journal of Islamic Studies, [S.l.], v. 11, n. 1, p. 33-54, may 2020. ISSN 2581-0146. This article has been retracted by Publisher based on the following reason: The Editor of HIKMAH Journal found the double publication in the article publishing due to article's content similarity published in EL HARAKAH Vol 13, No. 2 (2011) URL: http://ejournal.uin-malang.ac.id/index.php/infopub/article/view/1888. Titled” SUNDA WIWITAN BADUY: Agama Penjaga Alam Lindung di Desa Kanekes Banten” with the same author who is Masykur Wahid. Based on clarification, Author of the article have admitted that she has published the same article published in EL HARAKAH Vol 13, No. 2 (2011).